Interpretation of external quality assurance results on liver function test - Rahma Widyastuti; Nur Vita Purwaningsih; Rinza Rahmawati Samsudin; Anindita Riesti Retno Arimurti (Journal of Natural Sciences and Mathematics Research, 2020)
The quality of laboratory examination results must always be guaranteed in the sense that it can provide a level of accuracy and precision that can be accounted for. Therefore, a study of External Quality Consolidation (PME) was conducted. The purpose of this study was to describe the results of External Quality Monitoring in the field of clinical chemistry parameters of Serum Glutamic Oxalocetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) at the Public Health Center Laboratory in the Surabaya area. The population in this study was a health center in the area of the Surabaya City Health Office with a sample of 15 health centers that had examinations in the field of clinical chemistry. The sample used in this study was normal level control serum which was measured on the parameters of Serum Glutamic Oxalocetic Transaminase (SGOT) and Serum Glutamic Pyruvic Oxalocetic Transaminase (SGPT). The results of data analysis showed that the percentage of PME levels of SGOT with good VIS criteria was 73.33%, sufficient criteria was 0%, less criteria was 6.67%, poor criteria was 20%. While the SGPT parameters good criteria are 53.33%, sufficient criteria are 33.33%, less criteria are 13.33%, poor criteria are 0%.©2020 JNSMR UIN Walisongo. All rights reserved.